“Troubled home”: Displaced place identity in the wartime works of Ukrainian artists - Nenko Oleksandra (Finland, 2025)
Artists working with issues of displacement, especially those who have experienced displacement themselves, can implement cognitive and performative actions to re-order, re-conceptualize, re-frame, and re-shape the identity of a home place.